Exploring Adaptive Learning Dimensions Through EFA and CFA Validation - Dinda Alya Maghfira; Rizki Hikmawan; Jaka Septiadi; Rochman Bambang Eko Saputro; Nissa Arrumaisha (FKIP - Universitas Riau, 2026)
The increasing demand for adaptive learning in vocational education highlights the need for valid instruments to measure its key constructs. Despite growing research on adaptive assessment, adaptive gamification, personalized feedback, and self-regulated learning (SRL), these constructs are commonly examined separately. This study addresses this gap by developing and validating an SRL based adaptive learning instrument that integrates them within a unified measurement framework. The instrument was constructed from four theoretical constructs: adaptive assessment, adaptive gamification, personalized feedback, and self-regulated learning. A total of 507 students participated in the study. Data were analyzed using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). From the initial 24 items, nine items with inadequate psychometric properties were removed during the validation process, resulting in 15 valid items. The EFA results revealed four latent factors, namely feedback awareness, self-regulation, regulation deficit, and adaptive motivation. CFA confirmed a good model fit (CFI = 0.98, TLI = 0.97, RMSEA = 0.051, SRMR = 0.038) and acceptable composite reliability. The findings indicate that adaptive learning is perceived as an integrated process across SRL phases. This study provides a validated instrument and a conceptual basis for future research in adaptive learning.